Teknik Edible Coating dengan menggunakan Campuran Gel Lidah Buaya dan Ekstrak Daun Psidium guajava L. untuk Mempertahankan Sifat Fisikokimia Buah Jambu Biji - Refilda Refilda; Riga Habib Ngestu; Emil Salim; Yefrida (Jurnal Riset Kimia, 2022)
The synthetic chemicals is a common substance used to extend the shelf life of postharvest fruit. But it can have health impact. The use of edible coatings from natural ingredients has begun to be developed. Modification of aloe vera gel by guava leaf extract as the edible coating to increase guava fruit shelf life has not been reported yet. Guava fruit coated by several compositions of aloe vera gel and guava leaf extract have been carried out. Observations on physichochemical in fruit on the days 0, 3, 6, 9, 12 and 15 were evaluated. The best quality found on guava fruit treated with the compotition of aloe vera gel:ethanol guava leaf extract: CMC:glycerol (90: 5:0.25: 0.5) on the day 15. It had a weight loss of 9.88%, a spoilage of 3.33%, the decrease of water content 11.61%, titratable acidity 0.5%, total antioxidant 1.08 mg AA/g FW, total phenolic 0.51 mg GAE/g FW, and increase of total dissolved solids 3.01 oBrix. This result was significantly better than the uncoated fruit. It can be concluded that guava leaf extract can be used to maintain the physicochemical properties during storage.